The Assessment and Comparison of Tall Buildings with Outrigger and Belt Truss Systems Using Fragility Curves - Hamed Hamidi; Jafar Pakdaman; Ehsan Jahani; Hamid Rajabnejad (Journal of Structural and Construction Engineering, 2018)
In the design of high-rise buildings, three parameters such as resistance, hardness and stability are very important and when the height of building rises, effect of toughness and stability in optimum design will be dominate more than of the effects of these two factors against the lateral loads from wind and earthquake. The best ways to satisfy these two factors is the use of innovative forms and models of structures, so that, while maintaining stiffness, reducing deformation and drift caused by lateral loads, increase the stability of the structure. Outrigger and belt truss system are one of the innovative systems in high-rise structures that use it substantially reduces the consumption of structural steel and construction costs are high.In this research, two 2D frame with 5 spans and 30 and 50 stories according to the Iranian codes were designed in two cases of: the moment frames and frames with outrigger and belt with. Then maximum displacements of nodes and maximum inter stories drifts calculated for every earthquake records with use of SAP2000 software and time history analysis and has defined three different threshold IO, LS, and CP and acceleration of each record based on the severity of the earthquake. Then curves were plotted for each case; the results indicate that the outrigger and belt truss system would reduce the maximum inter story drift about 12 to 28 percent.